Increasing the efficiency of teaching the topic "Burns, frostbites, electric traumas" by means of modern educational technology. - Nor, N. N. (Medicni Perspektivi, 2013)
The main objective of the work is to test and implement modern interactive methods in the field of medical education, namely the method of cooperative groups into the educational process of the Department of General Surgery of SI "DMA MH" and to determine its efficacy by the example of class on the topic "Burns, frostbites, electrical trauma. Diagnosis, first aid, medical treatment”.The method is used to find similarities in different patterns of giving medical care to patients with burns, frostbites and electric trauma. Learning activity is divided into three stages. Stage 1: the teacher divides the students into four groups and gives a task to each group. Stage 2: each group announces the results and presents them in the standardized format. After the discussion the proper decision on the common features of the first aid, treatment, and the algorithm of action is made. Stage 3: the groups share results of the previous clinical experience, sum up, solve situational tasks and tests of level III. The method of co-operative groups allows to increase the motivation of students in the learning process, causes more efficient and thorough acquiring of the material, promotes development of clinical thinking, develops the urge towards collaboration and collective responsibility, favors the development of positive personal qualities of a future professional doctor.